Massive Congenital Vascular Tumor of Lower Limb: Kaposiform Hemangioendothelioma - Sarin, Yogesh Kumar; Kumar, Parveen (Journal of Neonatal Surgery, 2018)
We report a neonate with congenital Kaposiform hemangioendothelioma of left thigh and diagnostic dilemmas encountered in the management. The lesion was dealt with en-bloc resection in early infancy which was proven curative. Currently patient is doing well on follow-up.